Prediction of Zeta potential of minerals using tumbling method - Amparado, Stella Angela P. (2013)
This study aims to predict the zeta potential of a pure mineral against another pure macroscopic collector with known zeta potential as a function of pH and electrolyte concentrations. The Boltzmann equation is used as basis in the calculation of the magnitude of the predicted zeta potential. The pure minerals investigated are hematite (0.2542m average diameter) and titania (0.2116m average diameter); the macroscopic collector is silica (457.31m average diameter). Attachments behavior of minerals unto the collectors are conducted through the tumbling method. Tumbling is done at various pH conditions and using electrolyte concentrations of 0.0001M, 0.001M and 0.01M KNO3. Head suspensions are all at 100ppm and are tumbled at 38rev/min for 20minutes. Turbidity readings of head and after-tumbling solutions are used in determining the attached fractions of each system. The predicted iso-electic points (i.e.p.) for hematite, titania, and silica are at approximate ranges of pH 6-8, pH 4-6, and pH 3-4.5, respectively. Based on the results obtained for both hematite and titania, the magnitude of the zeta potential decreases as electrolyte concentration increases. For single component systems: a) the hematite-hematite suspension is stable at pH 9 and above, and unstable at pH 8 and below; b) titania-titania systems, dispersion is at ph 7 and above, while instability was observed at ph 6 and below; and, c) silica-silica systems, suspensions are stable at pH 4 and above while unstable at pH 3 and below. For two component systems: a) hematite-silica has stable suspensions at pH 8 and above while unstable at pH 7 and below; b) titania-silica is at pH 6 and above and coagulation at pH 5 and below. As the electrolyte concentration of the suspension and Hamaker constant of the material increases attraction also increases. On the other hand, as the zeta potential and particle size increases, higher energy barriers are formed, thus repulsion also increases. Inter-particle behaviour is analysed and interpreted using the classical DLVO theory.